Cross-sectional study of life satisfaction among elder Malaysian: comparison gender and race - Mardan, Homa; Tengku Abdul Hamid, Tengku Aizan; Mansor, Mariani; Abdullah, Siti Farra Zillah (Kementerian Pendidikan Malaysia, 2013)
Elder life satisfaction (ELS) as the characteristics of well being and quality of life is an important psychological concern. However, little is known about life satisfaction in multi-community society such as Malaysia with a variate ethnicity that may seem with different level among community- dwelling populations. The study aim was to identify the differences level of life satisfaction between gender and ethnicity. Population based study conducted in 2008 with 1077 participating. Subject with the population of 480 elderly filled the questionnaire successfully. The reported group related to perception, experience and awareness of elder abuse in Malaysian population comprises of three major ethnicity Malay, Chinese and Indian living in community dwelling in four zones Perak, Selangor, Kelantan, and Perak. This study based on secondary data is about the situation of life satisfaction among elderly in community-dwelling. T-test and ANOVA were utilized to assess level of life satisfaction among them. The results revealed that despite of different level of life satisfaction in some country with different race, in this study, in Malaysian population, there was no significant different level of life satisfaction among Malay, Chinese and Indian and also in terms of gender. Average life satisfaction among all of participation was about 6-7 from 10 that mean people in this community have moderate level of life satisfaction of life. In order to increase this level, it should be considering same programs for men and women and also in different ethnicity Moreover, identification of factors related to increase/decrease elder life satisfaction suggested.